Improving Students’ Vocabulary Mastery by Using Cooperative Learning Method Type Teams Game Tournament (TGT) - Karman Karman; Indriani Indriani (Universitas Pahlawan Tuanku Tambusai, 2021)
This research was conducted to improve students’ vocabulary mastery using cooperative learning method type teams game tournament (TGT) at the second grade of SMP Negeri 1 Pomalaa. This study used a classroom action research (CAR) design. The procedure of CAR consisted of preliminary of the research, planning, implementation, observation, analysis and reflection. Observation sheets and vocabulary test were used to gather the data. This research consisted of two cycles in which there was an improvement from cycle one to cycle two. The improvement could be seen on the result of the vocabulary test in cycle one and cycle two. It was found out that there was an improvement of students’ vocabulary mastery from cycle one to cycle two. In the cycle one, the percentage of students who passed the test was 47.36% and in cycle two the percentage of the students who passed the vocabulary test was 89.47%.